ANALISIS PENGGUNAAN KEIGO DALAM DRAMA DI MUSIM GUGUR KOUNODORI SEASON 1 - Prahesti, Natya Yoga (Chi'e: Journal of Japanese Learning and Teaching, 2020)
As a Japanese language learner requires mastering the language of respect (keigo) which is not only from learning in the classroom but can through television dramas containing respectful language to be used as learning models can be used by Japanese language learners. One of them is in the drama titled "Kounodori Season 1". This study aims to describe the type of keigo and the situation of using keigo in the autumn drama "Kounodori Season 1". The research approach uses a qualitative descriptive approach. The research technique used was the note and note technique. The results of this study are the use of keigo in the drama Kounodori Season 1 classified based on three types of keigo namely sonkeigo type, kenjougo type and teineigo type, found 45 data with 19 sonkeigo data types, kenjougo 6 data type and 20 teineigo data types. From these data it is known that the use of keigo in the drama Kounodori Season 1 that is often used is the type of teineigo keigo by taking into account several aspects such as intimacy, age, and status.